A regionally disaggregated inventory of nitrous oxide emissions from agricultural soils in Germany – a GIS-based empirical approach - Brocks, Sebastian; Jungkunst, Hermann F.; Bareth, Georg (ERDKUNDE, 2014)
Nitrous oxide (N2O) is a potent greenhouse gas, which has to be included in national inventories because it is contributing to global warming. It primarily originates from agriculturally managed soils. These represent area sources, which are much more difficult to account for than point sources, such as power plants or industrial sources. The Intergovernmental Panel on Climate Change provides a default emission factor but also the plea for more sophisticated ways of calculating N2O emissions from agricultural land use, in particular from industrialized nations. To fulfill this plea, already some approaches developed for use in Germany and elsewhere, which are more process based to a certain degree, have been published. However, these predominately require a high information input for model runs and site-specific calibration. In the present paper, we demonstrate the advantage of an empirical approach. This contribution introduces an approach for estimating N2O emissions in a regionally disaggregated manner by calculating emission factors based on 86 empirical measurements of N2O fluxes. These emission factors are calculated separately for distinct regions of Germany based on climate characteristics (precipitation and days of frost) and soil aeration. By combining these calculated emission factors with datasets on land use, nitrogen input, climate characteristics and soil, the N2O emission fluxes for Germany are estimated in a spatially disaggregated manner at the county (Landkreis) level, only accounting for agricultural land use and excluding forest and urban areas. This approach yields an emission estimate of 53.38 Gg N2O−N. For comparison purposes, this contribution also estimates N2O emissions using a spatially disaggregated version of the IPCC guidelines to determine emissions for the national greenhouse gas inventories, which results in an estimated emission of 35.70 Gg N2O−N for Germany. The results of these emission estimates suggest that the N2O emissions from agricultural land use are underestimated in the official national greenhouse gas inventory if the simple, single-emission-factor based method is used.